STUDI EKSPLORATIF TENTANG PRAKTIK SISTEM MANAJEMEN PERSEDIAAN DAN PERENCANAAN MATERIAL DALAM MENINGKATKAN EFISIENSI PROYEK KONSTRUKSI DI PT SEKAWAN JAYA - Syihabuddin, Muhammad; Tuti, Putri Andreas (Jurnal Ilmu Akuntansi, 2025)
This study aims to explore how inventory management systems and material planning practices influence construction project efficiency at PT Sekawan Jaya Jembrana. The research addresses problems related to inaccurate stock data, design changes, and delays in material supply that often lead to project inefficiencies and increased costs.A qualitative exploratory approach was employed using in-depth interviews, field observations, and document analysis. Data were collected from seven key informants, including project managers, procurement officers, warehouse staff, and site coordinators. The data were analyzed through thematic analysis to identify patterns, challenges, and strategies related to material management and planning practices.The findings reveal that the company’s inventory management system remains largely manual and unintegrated, causing frequent mismatches between recorded and actual stock levels (around 30%). Design modifications occurring during construction led to material overstocking by up to 15% and project cost overruns of approximately IDR 500 million. Moreover, inefficiencies in material handling and poor coordination among departments contributed to project delays of up to three weeks.This study concludes that non-digitalized inventory and material planning systems are key contributors to inefficiency in construction projects. Implementing an integrated, cloud-based Enterprise Resource Planning (ERP) system could enhance real-time data visibility, streamline coordination, and improve overall project performance. The study highlights the need for digital transformation and human resource training as essential steps toward achieving sustainable project efficiency.